The area of triangles enclosed by the axis and the tangent to
y
=
x
1
is always constant, no matter what
x
you pick. Find the value of this area.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Actually, you gave the solution in the problem itself when you said that tangent at any point gives the same area! One can take an easy point such as (1,1) to calculate the area.
Yes, but I wanted to show why that area was constant in my answer.
In the point of intersection the value is 1, about y=1/x the value of the x and y is 1. forms two right triangles equal to 1 peccaries and a square edge 1 also.
By co-ordinate geometry, the vertex is (1,1). The asymptote being y = x and the slope of the tangent touching the vertex is -1. So the tangent equation becomes y = 2 − x where x and y intercepts are (2,0) and (0,2) respectively. Hence the area is 2 1 × 2 × 2 = 2 . □
y ′ = − x 2 1 at point (1,1), the tangent line has equation: y=-x+2, this line cut X axis at (2,0) a r e a = ∫ 0 2 d x ∫ 0 − x + 2 d y = 2
We can think about this problem starting with two functions: y = 1/x and y = mx + b (this comes We can think about this problem starting with two functions: y = 1/x and y = mx + b (this comes from the tangent line). We can then substitute y with 1/x in the second equation, giving us 1/x = mx + b. We can now turn this into a quadratic equation and set it equal to zero. x ( 1 / x ) = x ( m x + b ) 1 = m x 2 + b x m x 2 + b x + 1 = 0
Now, lets say that the tangent line's y-intercept is b and its x-intercept is a. The b in y=mx+b is now the same as this b. This gives us the slope -b/a that we can now plug into the quadratic equation
−
b
/
a
x
2
+
b
x
+
1
We can now plug this into the quadratic formula.
(
−
b
±
√
b
2
−
4
[
−
b
/
a
]
[
1
]
)
/
2
However, since the function I only touches the tangent line ONCE, there can only be one answer. Because this is a quadratic, in order to have only one answer, the discriminant must equal zero. So we set the discriminant equal to zero.
b 2 − 4 [ − b / a ] = 0 b 2 = 4 b / a b = 4 / a b a = 4
Because the area of a triangle is 1/2 bh (1/2ba for this triangle), the answer is simply half of the above equation.
2 1 b a = 2
The area of the triangle is 2.
A = (1,1) We write the beam of the straight line that switches for A and is tangent to y=1/x.. y-1=m(x-1) 1/x -1 = mx - m 1-x=mx^2-mx mx^2-x(m-1)-1=0 Δ=0 m^2+2m+1=0 (m+1)=0 m=-1 We replace in the beam and we have y=-x+2. So the others points are B=(0,2) C=(2,0) . We've have a triangle with 2 cathetus of 2 unities. So area is 2x2/2= 2
y=1/x => slope at any point, dy/dx = -1/x² at any point (x₀, y₀), dy/dx = -1/x₀² => tangent line is y = (-1/x₀²)x + c since the tangent line satisfies by (x₀, y₀) => c = y₀ + (1/x₀) so, the equation is, y = (-1/x₀²)x + y₀ + (1/x₀) now find x and y axis cut point, when x = 0, y = y₀ + (1/x₀) when y = 0, x = y₀x₀² + x₀ so, Area = (½).(y₀x₀² + x₀).{y₀ + (1/x₀)} = (½).(1+x₀y₀)² But, y₀ = 1/x₀ => x₀y₀ = 1 => Area = (½).(1+1)² = 2
At the point (1,1), the base=height= 2
After using the formula A = 2 1 b h
the final answer is 2
Since the area is given to be constant we take the simple case of x=1 so y=1 and the slope of the tangent =-1/x^2=-1 so the equatiopn of tangent is x+y=2 having intercepts of 2 units on both the axis.The area is equail to 1/2 2 2=4/2=2 sq units.
Why are u guys making it look so hard put X axis as X then y=1÷X then put those values in the area rule and simplify😆
Problem Loading...
Note Loading...
Set Loading...
First thing, the slope of the tangent line is the derivative evaluated at the point of intersection. We know that: d x d x 1 = − x 2 1 . So the slope of the tangent line at the point x 0 is: Slope of the tangent line at x 0 = − x 0 2 1 . From this, we can find the x -intercept by setting y = 0 and solving using the slope-point formula: y − y 0 = − x 0 2 1 ( x − x 0 ) y = 0 0 − y 0 = − x 0 2 1 ( x − x 0 ) ⇒ − x 0 1 = − x 0 2 1 ( x − x 0 ) = − x 0 2 x + x 0 2 x 0 ⇒ − x 0 1 = − x 0 2 x + x 0 1 ⇒ x 0 2 x = x 0 2 ⇒ x = 2 x 0 . So the point of intersection with the x -axis is x = 2 x 0 , by symmetry, the y -intercept is y = 2 y 0 since y = x 1 ⟺ x y = 1 ⟺ x = y 1 . The area of a triangle is 2 1 h b , so the area of our triangles is: 2 1 2 x 0 ⋅ 2 y 0 = 2 x 0 y 0 = 2 x 0 ⋅ x 0 1 = 2 . See the image here to understand some of the notation:
http://i.stack.imgur.com/06y57.png